NP-011 Medication reconciliation in an emergency department – process assessment for a more efficient service. (24th March 2020) - Dreetz Holt, M; Teigen, A; Hermann, M; Kjome, R
Abstract : Background and importance: Medication reconciliation (MR) is the process of providing an exact and accurate list of all medications a patient is taking. This process is necessary to ensure that patients get the correct medications when admitted to hospital, thus preventing drug related problems. The pharmacists in the emergency department at Stavanger University Hospital use a method based on IMM-methodology (Integrated Medicines Management) when executing MR. This is time consuming, partly due to asking patients open questions and the lack of electronic resources available at the time IMM-methodology was developed. Aim and objectives: This thesis aims to make the pharmacist's method for MR at the emergency department more efficient, thus obtaining correct medicine lists as early as possible for more patients. Materials and methods: An observation study surveyed possible improvements in the established method for MR at Stavanger University Hospital. This subsequently led to implementing a revised method for MR through an intervention study, comparing the methods with efficiency (time usage/patient) and quality (proportion of patients with discrepancies and number of discrepancies per patient). The revised method was deemed not qualitatively inferior to the established method if the proportion of discrepancies had a maximum deviation of 10%. Results: In total two hundred patients (78 years ± 10, 58% women) were included in the control group and currently hundred patients (78 years ± 9, 50% women) in the intervention group. The time usage for completing a MR in the intervention group was reduced by 34% compared to the control group. There was no difference in the proportion of patients with discrepancies/number of discrepancies per patient (respectively 79%/1.9 in the control group and 80%/1.9 in the intervention group). Conclusion and relevance: Data from the first 100 patients in the intervention group shows that the revised method for performing MR makes the process more efficient without significantly deterioration of quality.